2018
DOI: 10.1097/md.0000000000010549
|View full text |Cite
|
Sign up to set email alerts
|

Fatal malignant pertussis with hyperleukocytosis in a Chinese infant

Abstract: Rationale:Pertussis has re-emerged on a global scale and is an ongoing public health problem, even in countries with high rates of vaccination. Hyperleukocytosis [white blood cell (WBC) count >100 × 109/L] is a rare complication that strongly predicts mortality in cases of severe pertussis.Patient concerns:We report a case of severe pertussis in an infant who initially presented with persistent cyanotic cough, tachypnea, and grunting. The infant's condition deteriorated rapidly, and she was transferred to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 22 publications
0
16
1
1
Order By: Relevance
“…Could death be reduced by rapidly reducing leukocytes and lymphocytes in patients with severe pertussis? In 2004, Romano et al published the first report on ET in a patient with severe pertussis [21]; thereafter, ET has been reported in multiple case reports of severe pertussis treatment [22][23][24][25][26][27][28]. According to previous research, although there is a lack of a unified standard, ET showed potential therapeutic benefits and promising results and is worthy of future exploration [18,21,25,27,29].…”
Section: Discussionmentioning
confidence: 99%
“…Could death be reduced by rapidly reducing leukocytes and lymphocytes in patients with severe pertussis? In 2004, Romano et al published the first report on ET in a patient with severe pertussis [21]; thereafter, ET has been reported in multiple case reports of severe pertussis treatment [22][23][24][25][26][27][28]. According to previous research, although there is a lack of a unified standard, ET showed potential therapeutic benefits and promising results and is worthy of future exploration [18,21,25,27,29].…”
Section: Discussionmentioning
confidence: 99%
“…This awaits con rmation in future work and exploration of related targeted treatment. Studies have shown that plasma exchange and leukapheresis can reduce leukocyte count and signi cantly improve fatal hypoxemia and pulmonary hypertension [23,24]. Some researchers have used carbon monoxide and sildena l to dilate pulmonary blood vessels and reduce pulmonary hypertension; some e cacy was observed [25].…”
Section: Discussionmentioning
confidence: 99%
“…Malignant pertussis is associated with respiratory failure, pulmonary hypertension, hyperleukocytosis, cardiogenic shock, and death. 1,4 The pathophysiological mechanism that mediates malignant pertussis is incompletely understood. A major part is attributed to the pertussis toxin (PT).…”
Section: Discussionmentioning
confidence: 99%